2004
DOI: 10.1111/j.1572-0241.2004.04057.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing The Development of Barrett's Epithelium in The Esophageal Remnant Postesophagectomy

Abstract: The development of Barrett's epithelium is frequent after esophagectomy, is time-related, reflecting chronic acid and bile exposure, and is not specific for adenocarcinoma or the presence of previous Barrett's epithelium. This model may represent a useful in vivo model of the pathogenesis of Barrett's metaplasia and tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 22 publications
2
67
1
4
Order By: Relevance
“…NSAIDs inhibit COX-2, which can be activated by proinflammatory cytokines, including interleukin-1h (IL-1h) and tumor necrosis factor-a (TNF-a), following mucosal injury. Overexpression of IL-1h has been reported in patients with esophagitis, Barrett's esophagus, and esophageal adenocarcinoma (42), and overexpression of TNF-a has been reported in patients with Barrett's esophagus (43). Exposure of the distal esophagus to acid reflux and components of bile reflux has been associated with the activation of COX-2 (44)(45)(46).…”
Section: Nsaids and Esophageal Adenocarcinomamentioning
confidence: 99%
“…NSAIDs inhibit COX-2, which can be activated by proinflammatory cytokines, including interleukin-1h (IL-1h) and tumor necrosis factor-a (TNF-a), following mucosal injury. Overexpression of IL-1h has been reported in patients with esophagitis, Barrett's esophagus, and esophageal adenocarcinoma (42), and overexpression of TNF-a has been reported in patients with Barrett's esophagus (43). Exposure of the distal esophagus to acid reflux and components of bile reflux has been associated with the activation of COX-2 (44)(45)(46).…”
Section: Nsaids and Esophageal Adenocarcinomamentioning
confidence: 99%
“…Barrett’s esophagus has been reported to arise de novo in patients who have previously undergone gastric pull-up esophagectomy [126,127,128,129,130,131]. In this procedure, the normal squamous epithelium of the cervical esophagus is interposed to the acid secreting mucosa of the gastric body.…”
Section: Development Of Columnar Mucosa After Esophagectomymentioning
confidence: 99%
“…Some reports even consider that reflux symptoms actually have no value in predicting the existence of reflux-related injury in esophageal remnant (15,22). Notably, 16% of patients in our longitudinal study developed metaplasia in the remnant esophagus, the prevalence was much less than that in western countries (20,23). We previously investigated the difference of mucosal damage in the esophageal remnant after esophagectomy and gastric interposition between Chinese and Canadian population, revealing that Canadian population was more sensitive to the gastroesophageal reflux damage compared to Chinese population, which might be attributed to the different genetic backgrounds (24).…”
Section: Discussionmentioning
confidence: 62%
“…Gastroesophageal reflux is a common complication after esophagectomy and esophagogastrostomy, which could eventually result in damage to esophageal remnant. Several studies have reported that esophagectomy with gastric pull-up would increase the development of esophagitis and also Barrett's epithelium (19)(20)(21). Therefore, esophagectomy with gastric interposition may represent a good in vivo model for the pathogenesis of GERD.…”
Section: Discussionmentioning
confidence: 99%